Analisis Pengaruh Iklim Organisasi, Kepemimpinan, Dan Kepuasan Kerja Terhadap Kinerja Pegawai PT. Batugunung Mulia Putra - Maulana, Beni; Arifin, Zainal; Daud, Ibrahim (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
The phenomenon that occurs today at PT. Batu Gunung Mulia Putra Agro, Batu Ampar District, Tanah Laut Regency is still a lot of negative assessments of employees. The condition is that there are still employees who often come late to work, there are employees who are passive towards work, there are employees who are not on time in completing their work and there are still some employees who leave assignments during working hours without explanation. This condition causes problems for the leadership to reduce the level of employee satisfaction. This type of research is explanatory research, the expected goal of this research is to analyze the effect of organizational climate, leadership, and job satisfaction simultaneously on employee performance at PT. Batu Gunung Mulia Putra Agro, Batu Ampar District, Tanah Laut Regency. The results of the data analysis above, it is proposed to conclude that organizational climate has an effect on employee performance with sig (0.000). Leadership has an effect on employee performance with sig (0.036). Job satisfaction has an effect on employee performance with sig (0.000). Organizational climate, leadership, and job satisfaction simultaneously affect the performance of employees at PT. Batu Gunung Mulia Putra Agro, Batu Ampar District, Tanah Laut Regency.